Deep eutectic solvents for the purification of chloromycetin and thiamphenicol from milk. Issue 3 (13th January 2017) - Li, Guizhen; Zhu, Tao; Row, Kyung Ho
Abstract : Deep eutectic solvents were used in both dispersive liquid–liquid microextraction and solid‐phase extraction for the purification of chloromycetin and thiamphenicol from milk. In the dispersive liquid–liquid microextraction procedure, deep eutectic solvents mixed with chloroform at different ratios (0:1–5:1, v/v) were used as the extraction agent to optimize the procedure, and the ratio of 2:1 v/v was found to be the best extraction agent with 87.23 and 83.17% recoveries of chloromycetin and thiamphenicol, respectively. Furthermore, deep eutectic solvents were also used to modify molecular imprinted polymers in solid‐phase extraction procedure, and the polymers were used to purify chloromycetin and thiamphenicol from milk. Fourier transform infrared spectroscopy, and nuclear magnetic resonance spectroscopy were used to characterize the polymers. The solid‐phase extraction recoveries with deep eutectic solvents with molecularly imprinted polymers (chloromycetin and thiamphenicol, two templates), molecularly imprinted polymers (without deep eutectic solvents), and nonimprinted polymers (without a template) for chloromycetin were 91.23, 82.64, and 57.3%, respectively, and recoveries for thiamphenicol were 87.02, 79.03, and 52.27%, respectively. The recoveries of chloromycetin and thiamphenicol from milk in the solid‐phase extraction procedure were higher than using deep eutectic solvents mixed with chloroform as the extraction agent in the dispersive liquid–liquid microextraction procedure.